Identification of non-fatal injuries in the cartography of the municipality of pasto with the clustering technique (2017)
This paper presents one of the results of the research project that aims to detect patterns of violent and georeferenced events based on information stored in the Crime Observatory of the Municipality of Pasto (Colombia) with data mining techniques. In order to georeference each event and process it geographically, a geocoder of urban addresses of the municipality of Pasto was built, using a free software. This goecoder was integrated to a cartographic viewer, and when applying the clustering technique with the algorithm k-means, allowed to visualize and to identify patterns in areas of the municipality where the different violent events happen. This information will make it easier for government and security agencies to make effective decisions related to citizen security and the prevention of such events.